Mortality and causes of death after new-onset atrial fibrillation: a nationwide study. (19th May 2022) - Aro, A; Haukka, J; Halminen, O; Putaala, J; Linna, M; Mustonen, P; Hartikainen, J; Airaksinen, J; Lehto, M
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Sigrid Juselius Foundation Introduction: Atrial fibrillation (AF) is the most common sustained arrhythmia worldwide, and its prevalence is increasing with aging population. AF is associated with increased cardiovascular morbidity and mortality, but the prognosis of newly detected AF in the general population is not well established. Purpose: Using data from the large FinACAF-study, a comprehensive nationwide retrospective cohort study including all diagnosed Finnish AF patients, we studied one-year mortality after new-onset AF in the general population and determined the causes of death of deceased AF patients. Methods: All patients with new-onset AF in Finland 2007-17 were identified from nationwide primary care and reimbursements registries and hospitalization records. Baseline characteristics of these patients were determined, and their survival was followed from registries for one year. Principal cause of death was determined from death certificate's International Classification of Diseases (ICD-10) Codes. Results: A total of 229 321 patients with first-diagnosed AF were identified (50.0% female). Mean age of men and women with new-onset AF was 69.4 ± 13.4 and 77.1 ± 11.8 years, respectively (p<0.001 for difference). In men and women, hypertension had been diagnosed in 68.0% vs 80.4% (p<0.001), congestive heart failure in 15.4% vs 19.3% (p<0.001), diabetes in 22.5% vs 20.7% (p<0.001) and vascular disease in 27.2% vs 24.8% (p<0.001), respectively. Prior stroke or transient ischemic attack had occurred in 14.0% of men and 16.8% of women (p<0.001). During the one-year follow-up, 11.6% of men and 13.7% of women died (Figure). Most common cause of death in these patients was ischaemic heart disease (26.2% of all deaths), followed by malignancies (17.4%) and dementia (12.4%). Cerebrovascular diseases were responsible for 10.8% of mortality. Conclusion: In this population-based nationwide study, we demonstrated that one-eight of patients with new AF died within one year of the diagnosis. Ischaemic heart disease was most frequent cause of death.